2011
DOI: 10.1161/circep.111.964213
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Sick Sinus Syndrome With Atrial Inexcitability and Coronary Sinus Flutter

Abstract: ongenital sick sinus syndrome has been described sporadically. The syndrome may comprise various components of sinus bradycardia, atrial fibrillation, and right atrial inexcitability. [1][2][3][4][5][6][7] In the current case, detailed electrophysiological evaluation was undertaken with electroanatomic mapping of the right atrium and coronary sinus (CS) and of associated supraventricular arrhythmias. CaseA 37-year-old asymptomatic male physician from Mexico without any previous medical problems was referred af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Patients with primary atrial disease may show the entire spectrum of atrial arrhythmias; data documenting the arrhythmogenic substrate in humans are few. 6,7 In this study, the detailed 3D reconstruction of atrial anatomies with accurate estimation of volumes and shapes, the electroanatomic mapping of low voltages and scar areas, and the LGE-MRI identification of fibrosis provided in vivo demonstration of the pathologic substrate of atrial arrhythmias in primary atrial disease. The second contribution of our observation is the correlation between the extent of low voltages and scarring/fibrosis with the type of atrial arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with primary atrial disease may show the entire spectrum of atrial arrhythmias; data documenting the arrhythmogenic substrate in humans are few. 6,7 In this study, the detailed 3D reconstruction of atrial anatomies with accurate estimation of volumes and shapes, the electroanatomic mapping of low voltages and scar areas, and the LGE-MRI identification of fibrosis provided in vivo demonstration of the pathologic substrate of atrial arrhythmias in primary atrial disease. The second contribution of our observation is the correlation between the extent of low voltages and scarring/fibrosis with the type of atrial arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, monogenic arrhythmogenic atrial diseases are rarely identified. Current knowledge is still limited to and based on electrophysiological studies done in cell and animal models or with computational simulation and on electrophysiological evaluation in 2 single patients …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was abolished by ablation at the ostium of the coronary sinus and not within the muscular CS at the origin of the vein of Marshall. This may reflect propensity for arrhythmogenesis throughout the embryologic left sinus horn which yields the coronary sinus as well as the vein of Marshall 10 …”
Section: Discussionmentioning
confidence: 99%
“…Varma et al present a teaching rounds case of congenital atrial disease with sinus node dysfunction, areas of atrial tachycardia and atrial electrical inexcitability, consistent with extensive fibrosis illustrating the coexistence of multiple brady and tachyarrhythmias in this rare congenital atrial disease. 23 Cavotricuspid isthmus ablation guided by real-time magnetic resonance imaging. Piorkowski C,et al 24 Achieving conduction block in the common cavotricuspid isthmus is difficult in some patients due to anatomic constraints, as can also be encountered in other areas of the heart.…”
Section: Atrial Fibrillation and Fluttermentioning
confidence: 99%